Plan de marketing para la empresa Fc-Multipernos de la ciudad de Loja - Carrión Guerrero, Fausto Wilfrido (2014)
The marketing plan is a management process that allows you to develop and maintain a strategic direction that considers goals and resources of the organization with its changing market opportunities. We can now reveal that part of the business sector has lack of knowledge in the development and implementation of plans of development and production, which is reflected in the difficulty to determine sales strategies, determine the tastes and preferences of consumers, prices, promotions etc. The following investigative work, establishes development of a Marketing Plan for the company FC-Multipernos from the city of Loja, same that will allow them in the long term, achieve development and performance of its activities, in the prospect of obtaining better results in their daily work. Several objectives in which consists the elaboration of a Strategic Marketing plan that can help you achieve better positioning in the market in the city of Loja, are set to do so is a situational analysis. It should be noted that for the fulfilment of such objectives were applied methods to identify the theoretical references on the Strategic Plan; concepts, fundamentals and insights obtained from the same deductive method that allows to analyze external factors (opportunities and threats) at different levels of technological, social, political, economic and Administrative Sciences for the practical application of knowledge in addition five forces PORTER determining its impact on the company, on the other hand the inductive method allowed analyzing internal factors (strengths and weaknesses) to turn in that can be exploited. The techniques used were the direct observation, interview (Manager), survey (10 employees) and customers (320 people), and finally the analytical method which allowed for the situational analysis of the company in study in order to determine what are the strengths and weaknesses which owns and aspects that should be improved for the correct operation of the same. As favorable results have to the company f-c Multipernos % 74 offers quality products, given currently released only 100% by friends without using advertising media, although it maintains several competitive advantages as a location where 91% of customers recognise it. 60% say that they are unaware of the existence of the mission, vision, policy and business objectives, 100% of workers say not having the necessary freedom for decision-making problems with customers, which induces to the centralized management that delay and delay attention to customers. Finally presents the conclusions and recommendations which was reached, to propose and solve the problems facing the company and take advantage of opportunities provided by the market to grow and strengthen.